Ulipristal in Fibroids: A Recent Study - Alla Satyanarayana Reddy; S. Manjula (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Surgery is used to treat symptomatic uterine fibroids. The medical management involves Tranexamic acid, OC pills, Progesterone, LNG IUS, GnRH analogues, as a temporary measure pre operatively. SPRMs (Selective Progesterone Receptor Modulators) are a new class of drugs for medical use. Ulipristal acetate is an SPRM that has been clinically approved for the treatment of fibroids. The research was carried out at a tertiary care hospital in South India. The study’s subjects are fifty women with fibroids and menorrhagia who are awaiting definitive surgery or pre-operative treatment to prepare them for surgery or who want medical treatment. Blood loss was measured using the PBAC scale at the start of treatment. Ultrasonography was used to determine the number and size of the fibroids. Associated symptoms were documented. For three months, urlipristal acetate 5 mg was administered daily. At three months of treatment, blood loss, amenorrhoea, and fibroids volume were all measured. The side effects were documented. They were followed for another three months to see if their menstrual cycle had resumed. The average blood loss was reduced by 88%. Amenorrhoea affected 82 percent of women. The volume of the fibroids was reduced by 28.2 percent. There were no bad side effects. Hot flushes were experienced by two amenorrhic women. 47 returned to menstruation after 30-40 days, and the bleeding was normal or slightly less. There was relief from dysmenorrhea and fibroids’ pressure symptoms. The study’s findings were compared to those of other studies. In terms of controlling menorrhagia and shrinking fibroid size, a 5 mg dose of ulipristalis is just as effective as a 10 mg dose.